(untitled) (Mediscope, 2020)
Carcinoid of the pancreas is rare among children. We treated a debilitating child who complained about post-prandial pain with a mass in upper abdomen, vomiting and weakness for a period of six months. Abdominal examination revealed an immobile, mildly tender, solid mass in the right lumbar region. Ultrasonography of abdomen demonstrated a tumour of head of the pancreas and ultrasonography-guided fine needle aspiration cytology of the mass suggested a malignant small round cell tumour. With Computed Tomogram an enhancing compact big mass was found at the head of the pancreas compressing the duodenum without invasion and metastasis. At exploratory laparotomy, we also detected a well-defined, rounded, big solid mass arising from uncinate process of the pancreas with no metastasis. After the excision of the mass along with a healthy portion of uncinate process, the patient recovered successfully. Histopathology evaluation showed a neoplasm composed of small nests and sheets of a dense cluster of malignant round cells with hyperchromatic nuclei, sometimes forming acini with stromal invasion. Diagnosis was malignant carcinoid of the pancreas, T2 N0 M0. At follow-up of three and a half years, the patient was found symptom-free and there was no evidence of recurrence. Mediscope Vol. 7, No. 1: Jan 2020, Page 58-62